ANALISIS EFEKTIFITAS IMPLEMENTASI APLIKASI PEMBELAJARAN PENDIDIKAN ANTI KORUPSI BERBASIS MULTIMEDIA SEBAGAI UPAYA REVITALISASI NASIONALISME - Yani Prihati; Sinta Tridian Galih; Tri Karyanti (IST AKPRIND Yogyakarta, 2018)
Corruption has become a serious problem in Indonesia. Acts of corruption can be done anywhere, by anyone, and by the amount that tends to increase. This is why the government established the KPK as an independent institution that has the task of corruption action and prevention. As one form of implementation of preventive duties, the KPK organizes anti-corruption education programs at every level of education. This shows that the world of education is very important to be involved in combating corruption among the younger generation. The context of this research is to implement a multimedia-based anti-corruption education learning media that has been developed previously called MedPAK. The object of this research is 5 universities in Semarang, Pati, Salatiga and Pekalongan involving 273 students as respondents. The method used is survey. The tests were conducted to measure the effect of MedPAK on the outcomes of anti-corruption education learning outcomes. The result of the test shows that the implementation of MedPAK improves the total score of learning achievement of anti corruption education by 12.0% so it can be concluded that MedPAK can support the improvement of the quality of anti-corruption education as one of the nationalism revitalization efforts of towards the improvement of the nation's competitiveness.